Thermo- and Light-Responsive Polymer-Coated Magnetic Nanoparticles as Potential Drug Carriers - Cui, Guihua; Wang, Hao; Long, Shengsen; Zhang, Tianshuo; Guo, Xiaoyu; Chen, Shuiying; Kakuchi, Toyoji; Duan, Qian; Zhao, Donghai (Frontiers in Bioengineering and Biotechnology, 2022)
A series of thermo- and light-responsive copolymers of poly (N-isopropylacrylamide) (PNIPAM) and 6-[4-(4-methoxy phenyl azo)-phenoxyl-hexyl methacrylate) (AzoMA) (PNIPAM-b-PAzoMA) were synthesized via reversible addition–fragmentation chain transfer (RAFT) radical polymerization. The resulting copolymers had a narrow molecular weight distribution range of 1.06–1.24, in which Mn changed regularly with the monomer concentration. Subsequently, the diblock copolymers were successfully modified on the surface of iron oxide nanoparticles through the interaction between the chemical bonds to prepare Fe3O4@(PNIPAM-b-PAzoMA) nanoparticles. The size of fabricated nanoparticles with excellent thermo-sensitivity and photo-sensitivity was controlled at about 40–50 nm. Cell viability assays suggested that the nanoparticles showed no significant cytotoxicity and potential drug delivery in the tumor microenvironment.